The effects of azithromycin in treatment-resistant cough: a randomized, double-blind, placebo-controlled trial - Hodgson, David; Anderson, John; Reynolds, Catherine; Oborne, Janet; Meakin, Garry; Bailey, Helen; Shaw, Dominick E.; Mortimer, Kevin; Harrison, Tim (Elsevier, 2016)
Background